Diagnosis dan Tatalaksana Age-related Macular Degeneration - Gigaramadan Sema (Jurnal Medika Hutama, 2022)
Age-related Macular Degeneration (AMD) is a disease that attacks the retinal tissue and causes a progressive vision loss. AMD commonly appears in the elderly population with a global prevalence of 170 million and causes 8.7% of global blindness. Adequate knowledge of this disease is needed in establishing an accurate early diagnosis which is very important in determining the appropriate management and management of the patient to prevent and slow the progression of the disease. The diagnosis is made by various modalities such as fundoscopy, fluorescein angiography, and ocular coherence tomography (OCT). The recommended treatment is AREDS-2 supplementation and administration of anti-VEGF drugs. Follow-up and dosage adjustments are essential to ensure appropriate and effective treatment.